2022
DOI: 10.1002/anie.202210478
|View full text |Cite
|
Sign up to set email alerts
|

Less is More: A Shortcut for Anionocages Design Based on (RPO32−)‐Monourea Coordination

Abstract: Anionocages have been developed as a unique family of hydrogen bonded cages. However, strategies for constructing anionocages are mainly limited to that based on (PO 4 3À )-bisurea coordination, neither the ligands nor the anions lack the simplicity and diversity of the maturely developed analogues based on metal coordination (i.e. metallocage). We report herein a more simple strategy for anionocages design based on (RPO 3 2À )-monourea coordination, utilizing monourea rather than bisurea as the hydrogen bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…[20] In summary, we have developed an efficient strategy for the stereoselective synthesis of hydrogen-bonded cages, by . [10] In (c), the signal of H4 is partially overlapped by the Me signal of A 2R (◆). Enantioselectivity factors (K R /K S or K S /K R ) are shown as the insets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] In summary, we have developed an efficient strategy for the stereoselective synthesis of hydrogen-bonded cages, by . [10] In (c), the signal of H4 is partially overlapped by the Me signal of A 2R (◆). Enantioselectivity factors (K R /K S or K S /K R ) are shown as the insets.…”
Section: Methodsmentioning
confidence: 99%
“…To verify our design idea, TBA + (tetrabutylammonium) salts of phosphonomycin (antibiotics, A 1R ), (R/S)-tenofovir (antivirals, A 2R /A 2S ), adenosine monophosphate (natural product, AMP, A 3R ), and clindamycin phosphate (antibiotics, A 4R ) were selected to assemble with an achiral, bismonourea ligand L in MeCN (Scheme 1, please see Figures S1-S23 in Supporting Information for more details). [10] High-resolution ESI mass spectrometry (HRMS, Figures S24-S28) indicated that A 1R and A 2R /A 2S induced the formation of A 2 L 4 quadruple helicates (H 1R and H 2R / H 2S ), while A 3R and A 4R led to A 2 L 3 triple helicates (H 3R and H 4R ), which was attributed to the bulkiness of the chiral substituent group (R*) of A 3R and A 4R making an A 2 L 4 structure too crowded around the coordination center (Scheme 1, and Figure S29-S31). The 1 H NMR spectrum of each helicate showed one set of sharp signals, with the integral ratio of A : L consistent with that suggested by HRMS.…”
mentioning
confidence: 99%
“…Two A 2 L 4 quadruple helicates, 18 4 (PhOPO 3 ) 2 and 18 4 (HOPO 3 ) 2 , were obtained by the self‐assembly of bis‐monourea ligand 18 and PhOPO 3 2− or HOPO 3 2− anions, respectively (Figure 8). [36] Crystal structures of 18 4 (PhOPO 3 ) 2 and 18 4 (HOPO 3 ) 2 showed that PhOPO 3 2− or HOPO 3 2− anions were coordinated with four monourea groups through a total of 8 hydrogen bonds. Especially, PhOPO 3 2− anion also interacted with naphthyl groups of ligand 18 by 7 short interactions to further enhance the stability and improve host‐guest combinations.…”
Section: Anion‐coordination‐driven Helical Structuresmentioning
confidence: 99%
“…Two A 2 L 4 quadruple helicates, 18 4 (PhOPO 3 ) 2 and 18 4 (HOPO 3 ) 2 , were obtained by the selfassembly of bis-monourea ligand 18 and PhOPO 3 2À or HOPO 3 2À anions, respectively (Figure 8). [36] Crystal structures of 18 4 (PhOPO 3 ) 2 and 18 4 (HOPO 3 ) 2 showed that PhOPO 3 2À or HOPO 3 2À anions were coordinated with four monourea groups Figure 6. The crystal structures of M-15 3 (PO 4 ) 2 �R-G1, P-15 3 (PO 4 ) 2 �S-G1 and structures of choline and its derivatives, the chiral guest molecules.…”
Section: Anion-coordination-driven Helical Structuresmentioning
confidence: 99%
“…The majority of noncovalent cages are currently constructed through metal coordination, , anion coordination, , π–π stacking, and hydrogen bonds, among which metal coordination cages (abbreviated metallacages) are the most extensively studied. Saalfrank and co-workers reported the first metallacage in 1988, and since then, the groups of Fujita, Stang, Raymond, Nitschke, Shionoya, Clever, Yoshizawa, and others have successfully developed various coordination-based self-assembly protocols to build numerous metallacages.…”
mentioning
confidence: 99%